Identification of a novel stripe rust resistance gene from the European winter wheat cultivar ‘Acienda’: A step towards rust proofing wheat cultivation - Grover, Gomti; Sharma, Achla; Mackay, Ian; Srivastava, Puja; Kaur, Satinder; Kaur, Jaspal; Burridge, Amanda; Allen, Sacha Przewieslik; Bentley, Alison R.; Chhuneja, Parveen; Bains, N.S. (2022)
All stage resistance to stripe rust races prevalent in India was investigated in the European winter wheat cultivar ‘Acienda’. In order to dissect the genetic basis of the resistance, a backcross population was developed between ‘Acienda’ and the stripe rust susceptible Indian spring wheat cultivar ‘HD 2967’. Inheritance studies revealed segregation for a dominant resistant gene. High density SNP genotyping was used to map stripe rust resistance and marker regression analysis located stripe rust resistance to the distal end of wheat chromosome 1A. Interval mapping located this region between the SNP markers AX-95162217 and AX-94540853, at a LOD score of 15.83 with a phenotypic contribution of 60%. This major stripe rust resistance locus from ‘Acienda’ has been temporarily designated as Yraci. A candidate gene search in the 2.76 Mb region carrying Yraci on chromosome 1A identified 18 NBS-LRR genes based on wheat RefSeqv1.0 annotations. Our results indicate that as there is no major gene reported in the Yraci chromosome region, it is likely to be a novel stripe rust resistance locus and offers potential for deployment, using the identified markers, to confer all stage stripe rust resistance.